Moderasi Kinerja Lingkungan Pada Hubungan Green Accounting Dan Kinerja Ekonomi - Mochammad Ilyas Junjunan; Binti Shofiatul Jannah; Ade Irma Suryani Lating; Ajeng Tita Nawangsari (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to examine stakeholder theory and legitimacy with the triple bottom line approach on environmental aspects, by examining the direct effect of green accounting on economic performance and the moderating role of environmental performance on the relationship between green accounting and economic performance. A total of 90 data across 15 companies in the mining sector during the six annual report periods were used as sample. This sample were analyzed using an interaction moderation regression model. The results of the study show that the application of green accounting has a positive effect on economic performance, in addition environmental performance is able to quasi-moderate the relationship between green accounting and economic performance. The limitations of this study lies in the limited measurement of the GRI index on environmental performance aspects. Further more the limited scope of the corporate sub-sector put some generalizing issue. Future research is expected to use environmental performance indicators that can generalize results to other company sub-sectors. In addition, cross section data analysis is more relevant which is developed in the moderation of the analysis model.